Larval size of Strongylocentrotus purpuratus during laboratory experiments with different food treatments - Jasper Hildebrand; Meike Stumpp (PANGAEA, 2025)
Strongylocentrotus purpuratus (Stimpson 1857) originally collected in November 2022 from La Jolla, USA (Lat: 32.842674; Long: -117.257767) were held in flow-through tanks which were filled with water from Kiel Fjord adjusted to 31.5 psu in the Christian-Albrechts-Universität zu Kiel at 10 °C. For experimental characterization of carbohydrate digestion between September and November 2023, S. purpuratus larval cultures were maintained with two different food conditions (low food vs. high food) under low light conditions, following a 12-hour dark to 12-hour light cycle at 15°C, with continuous mixing facilitated by a gentle stream of pressurized air bubbles. Health assessments and larval size were conducted by sampling two 10 ml water samples at 0, 3, 5, 7, 9 & 10 days larval age.
In: Hildebrand, J; Stumpp, M (2025): Genetic and enzymatic analyses of carbohydrate metabolism in Strongylocentrotus purpuratus larvae [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.968977